Synthesis and evaluation of dapagliflozin ester prodrugs with improved hygroscopicity and thermal stability - Sung, Si Young; Chae, Yu Na; Lee, Dae Young; Kim, Kyeong Min; Kim, Eun Jung; Han, Ji Hye; Kim, Wook; Yoon, Sung Hwa (Letters in Drug Design and Discovery, 2020)
Background: Dapagliflozin, developed as an SGLT-2 inhibitor, has a low melting point and high hygroscopicity, which needs extreme care during pharmaceutical production to keep the active pharmacological property. Various attempts have been made to overcome these problematic properties. Objective: To develop dapagliflozin prodrugs that have similar pharmacological effects with improved hygroscopicity and thermal stability. Method: The novel dapagliflozin ester prodrugs containing pharmaceutically acceptable moieties were synthesized and their pharmacokinetics (PK) and physical properties were compared with dapagliflozin propanediol hydrate (DPD, Farxiga®). The PK in dog and rat, in vitro stability, hygroscopicity, and physical property studies in accelerated conditions (40°C, 75 % RH) were performed with prodrugs. Results and Discussions: Among the eight synthesized prodrugs, Cmax and AUC0-48h values of prodrug 8b (1.35 µg/ml and 14.78 µg·h/ml, respectively) were similar to those of DPD (1.67 µg/ml and 14.27 µg·h/ml, respectively). However, the rest of the prodrugs 8a, 8c, 8d, 8e, 8f, 8g and 8h showed significantly lower Cmax and AUC0-48h values than DPD. Prodrug 8b completely converted into parent drug in the body. Conclusion: The novel prodrug 8b exhibited comparative PK profile to that of DPD, but with low hygroscopic property and better thermal stability than DPD.
Keywords: Dapagliflozin; Diabetes; Farxiga®; Prodrug; SGLT-2 inhibitor; Thermal stability